2020 Consensus summary on the management of hypertension in Asia from the HOPE Asia Network. Issue 3 (9th December 2019) - Kario, Kazuomi; Park, Sungha; Chia, Yook‐Chin; Sukonthasarn, Apichard; Turana, Yuda; Shin, Jinho; Chen, Chen‐Huan; Buranakitjaroen, Peera; Divinagracia, Romeo; Nailes, Jennifer; Hoshide, Satoshi; Siddique, Saulat; et al.
Abstract: Hypertension professionals from Asia have been meeting together for the last decade to discuss how to improve the management of hypertension. Based on these education and research activities, the Hypertension, brain, cardiovascular and renal Outcome Prevention and Evidence in Asia (HOPE Asia) Network was officially established in June 2018 and includes experts from 12 countries/regions across Asia. Among the numerous research and review papers published by members of the HOPE Asia Network since 2017, publications in three key areas provide important guidance on the management of hypertension in Asia. This article highlights key consensus documents, which relate to the Asian characteristics of hypertension, home blood pressure monitoring (HBPM), and ambulatory blood pressure monitoring (ABPM). Hypertension and hypertension‐related diseases are common in Asia, and their characteristics differ from those in other populations. It is essential that these are taken into consideration to provide the best opportunity for achieving "perfect 24‐hour blood pressure control", guided by out‐of‐office (home and ambulatory) blood pressure monitoring. These region‐specific consensus documents should contribute to optimizing individual and population‐based hypertension management strategies in Asian country. In addition, the HOPE Asia Network model provides a good example of the local interpretation, modification, and dissemination of international best practice to benefit specific populations.